Genetic evaluation of different lactation milk yields in Sahiwal cattle - Singh, C.V.; Barwal, R. S.; B. Prakash (Journal of Livestock Biodiversity, 2025)
The present study was conducted on production records of 927 Sahiwal cows born to 72 sires, spread over a period of 28 years (1978-2007) maintained at Government Livestock Farm, Chakganjaria, Lucknow. The lactation yield from first to fifth lactations was evaluated. The overall least squares means of 1st, 2nd, 3rd, 4th and 5th lactation milk yields were 1468.61±40.98 kg, 1549.55± 32.07 kg, 1667.07± 34.32 kg, 1682.86 ±35.40 kg and 1601.39±36.59 kg, respectively. The period of calving had significant influence on all the lactation milk yields. Season effects were significant on 3rd, 4th and 5th lactation milk yields while non significant effects on 1st and 2nd lactation milk yield were observed. The heritability estimates of different lactation milk yields were moderate. The genetic and phenotypic correlations among all the lactation milk yields were observed from low to very high. The mean performance of different lactation milk yields exhibited an increasing trend.